Association between availability of non-prescription beta 2 agonist inhalers and undertreatment of asthma. Issue 6891 (5th June 1993) - Gibson, P; Henry, D; Francis, L; Cruickshank, D; Dupen, F; Higginbotham, N; Henry, R; Sutherland, D
Abstract : OBJECTIVE–To determine whether the availability of beta 2 agonist inhalers without prescription leads to undertreatment of asthma. DESIGN–Cross sectional study of adequacy of treatment in asthmatic subjects who purchased beta 2 agonist inhalers and subjects who obtained inhalers by prescription. SETTING–Community pharmacies in New South Wales, Australia. SUBJECTS–403 eligible consecutive asthmatic subjects aged 13 to 55 purchasing salbutamol metered dose inhalers over the counter or by prescription; 197 attended for follow up and spirometry and 139 returned 14 day symptom, peak flow, and medication diaries. MAIN OUTCOME MEASURES–Severity of asthma assessed on frequency of day time and night time wheezing, frequency of inhaler use, and peak expiratory flow rates. Adequacy of treatment according to published guidelines. RESULTS–Of the 139 patients who completed the diary 83, (60%) purchased their inhalers without prescription and 83 were undertreated. The characteristics of patients in the prescription and purchasing groups were similar. Multiple logistic regression analysis identified use of non-prescribed salbutamol as being associated with a 2.9-fold increase in the odds of undertreatment (95% confidence interval 1.3 to 6.8). Smoking increased the odds of undertreatment (3.3, 1.2 to 9.5) and use of a peak flow meter reduced the odds (0.11, 0.04 to 0.34). Adjustment for frequency of consultation made use of non-prescription salbutamol insignificant (1.4, 0.55 to 3.8). Attitudes to services provided by doctors and pharmacists were favourable and not associated with undertreatment. CONCLUSION–Over the counter purchase of salbutamol is associated with infrequent consultation with doctors and undertreatment of asthma.